2021
DOI: 10.1111/bju.15499
|View full text |Cite
|
Sign up to set email alerts
|

Growth and renal function dynamics of renal oncocytomas in patients on active surveillance

Abstract: To study the natural history of renal oncocytomas and address indications for intervention by determining how growth is associated with renal function over time, the reasons for surgery and ablation, and disease-specific survival. Patients and MethodsThe study was conducted in a retrospective cohort of consecutive patients with renal oncocytoma on active surveillance reviewed at the Specialist Centre for Kidney Cancer at the Royal Free London NHS Foundation Trust (2012 to 2019. Comparison between groups was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Oncocytomas represent the most common surgically removed benign renal tumors, with an incidence ranging from 4% to 7% of all kidney surgeries for neoplasms [ 184 ]. This high rate of surgery for a non-malignant process is the result of the underuse of percutaneous renal surgery and from the inability of the current radiological techniques to distinguish between malignant and benign lesions with an acceptable degree of accuracy [ 184 , 185 ].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncocytomas represent the most common surgically removed benign renal tumors, with an incidence ranging from 4% to 7% of all kidney surgeries for neoplasms [ 184 ]. This high rate of surgery for a non-malignant process is the result of the underuse of percutaneous renal surgery and from the inability of the current radiological techniques to distinguish between malignant and benign lesions with an acceptable degree of accuracy [ 184 , 185 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Oncocytomas represent the most common surgically removed benign renal tumors, with an incidence ranging from 4% to 7% of all kidney surgeries for neoplasms [ 184 ]. This high rate of surgery for a non-malignant process is the result of the underuse of percutaneous renal surgery and from the inability of the current radiological techniques to distinguish between malignant and benign lesions with an acceptable degree of accuracy [ 184 , 185 ]. Moreover, in the urological scenario, clinicians are still divided on the interventional management of oncocytoma, with a high percentage of surgeons who prefer to operate rather than considering a period of surveillance [ 186 ].…”
Section: Treatmentmentioning
confidence: 99%
“…A total of 2862 initial searches were identified. After duplicate removal, title and abstract screening, and full-text review, ten studies were included for qualitative and quantitative analyses [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] .
Fig.
…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Six studies including 433 patients reported the definitive treatment rates from AS to definitive treatment [12] , [13] , [14] , [17] , [18] , [19] . In the pooled studies, the median follow-up was 34.5 mo (95% confidence interval [CI] 30.6–38.4).…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation